STUDY ON THE USE OF DATA MINING TECHNOLOGY FOR ELECTION CAMPAIGNS IN INDONESIA - Maulana, Wisnu Sukma; Dwi Kartinah (International Journal Science and Technology, 2024)
Indonesia adheres to democracy with a presidential government format. From the beginning of the reform era in Indonesia, the system of electing government representatives in the realm of council members, regional heads, and heads of state was carried out by looking for direct elections. Direct elections are carried out with several stages starting from registration, campaigning, elections, to the decision to recapitulate the winner's vote. One of the ways that candidates for election participants do is to campaign massively to the public. This campaign is expected to introduce the candidate to be the top choice of the community. The biggest challenge of this massive campaign is how much it costs compared to the reach of socialization to the community. Campaigns in conventional forms such as banners and social assistance do not necessarily make the election participants win an election, especially when the campaign funds have been enlarged to exceed the competitor who won the election. With the existence of social media, which is developing quite rapidly today such as Facebook, Instagram, Twitter (x), TikTok, and so on, election participants have used social media as an alternative and even the main campaign media. The next challenge is how the use of social media can produce significant results in the campaign of election participants. One of the sciences in the world of technology is data mining. Data mining helps in processing data to provide decision references that are in accordance with the sampling conditions of the conditions taken from the data. The purpose of this journal is about the utilization of data mining technology in helping election campaigns with social media to the factors involved in this in the current era of Indonesian democracy.